Religious Conflict in Terms of Martin Heidegger's Philosophy of Existentialism - Adi Tri Pramono (Yayasan Rumah Peneleh, 2020)
This paper aims to provide an overview of the process and construction of religious conflict, including genealogy, forms, and analysis of religious conflict causes. Further, this research also provides an in-depth analysis of religious conflicts from Martin Heidegger's existentialist philosophy. The methodology employed in this paper is hermeneutics. The research result indicates that the root of religious conflict is fear in facing increasingly modern life. The existence of this fear reduces the presence of the possibility. In the context of Martin Heidegger's existentialist philosophy, the experience is a process of being as Dasein to exist. Therefore religious conflict tends to be taken as a priority decision due to the lack of awareness of existential possibilities. The paper contributes to society in the sense that education must be accessible without any obstacles because, through knowledge, a broader perspective can be obtained since the right to education must be placed prior the right to exist.